Monitoring system for the effective instruction based on the semi-automatic evaluation of programs during programming classroom lectures - Kogure, Satoru; Nakamura, Riki; Makino, Kanae; Yamashita, Koichi; Konishi, Tatsuhiro; Itoh, Yukihiro (Research and practice in technology enhanced learning, 2015)
In this study, we developed a programming practice monitoring system to facilitate teachers to give appropriate instructions to students at the appropriate time during classroom lectures. To help teachers to provide appropriate instruction to learners, we identified parameters that would be useful for teachers during programming exercise in classroom lecture. We constructed a monitoring system with five functions. The system automatically acquired the programs written by students to evaluate their performance, and the teacher can obtain their performance using the five functions. We asked four subjects to test our proposed monitoring system during a simulation of a classroom lecture. The evaluation revealed that the system had a high accuracy in evaluating student programs.